The influence of leadership style and employee loyalty on organizational commitment at pt pamungkas putra pratama in cilegon, banten - Azzahra, Anneira; Maliki, Budi Ilham; Fauzi, Ade (Institute of Computer Science (IOCS), 2025)
The construction industry is one of the strategic sectors that plays a crucial role in national economic development. The success of construction companies depends not only on capital and technology but also on the quality of human resources who demonstrate strong commitment and high loyalty. This study aims to analyze the influence of leadership style and employee loyalty on organizational commitment at PT Pamungkas Putra Pratama. The method used is a survey method with a quantitative approach. The sample consisted of 54 respondents selected using a simple random sampling technique. Data were analyzed using multiple linear regression with the aid of SPSS software. The results of the study show that leadership style and employee loyalty have a significant influence on organizational commitment. This is indicated by the coefficient of determination (R²) of 74.9%, suggesting that leadership style and employee loyalty jointly influence organizational commitment by 74.9%. In addition, the simultaneous test (F-test) produced an F value of 76.270 with a significance value of 0.000 (< 0.05), indicating a statistically significant simultaneous effect of leadership style and employee loyalty on organizational commitment. These findings affirm the importance of effective leadership and employee loyalty in enhancing organizational commitment. This research provides a new perspective on how a combination of effective leadership styles and employee loyalty can improve organizational sustainability in the manufacturing sector. These findings are expected to serve as a reference for management practitioners in designing leadership strategies that foster employee loyalty and strengthen organizational commitment